2005
DOI: 10.1111/j.1444-0938.2005.tb06701.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and morbidity of hospital‐presenting corneal infiltrative events associated with contact lens wear

Abstract: Overall, there is an eight times higher incidence of CIEs in wearers who sleep in contact lenses compared with wearers who use lenses only during the waking hours. For those who choose to routinely or intermittently sleep in soft contact lenses, silicone hydrogels are the lens of first choice because CIEs are less clinically severe with this lens type compared with hydrogel lenses. The rate of significant visual loss as a result of developing a CIE is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…Previous studies have shown that overnight contact lens wear and the use of extended wear contact lenses are associated with an increased risk of microbial keratitis [4] and corneal infiltrative events [5]. Almost half (49 %) of the patients in our study had some risk factor for development of CLRCs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that overnight contact lens wear and the use of extended wear contact lenses are associated with an increased risk of microbial keratitis [4] and corneal infiltrative events [5]. Almost half (49 %) of the patients in our study had some risk factor for development of CLRCs.…”
Section: Discussionmentioning
confidence: 92%
“…Although contact lenses are considered safe, it is not rare for patients to develop contact lens-related problems particularly when contact lens care is not meticulous. It has been estimated that about 6-21 % of contact lens wearers develop a contact lens-related complication each year [3,4]. The severity of these problems can range from mild corneal epitheliopathy to vision-threatening microbial keratitis.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors reported that asymptomatic lens wear for extended periods did increase ocular microbiota (Larkin et al, 1991;Hart et al, 1993) and others reported that asymptomatic lens worn for extended periods did not increase normal ocular microbiota (Gopinathan et al, 1997;Willcox et al, 1997). However, Efron et al (2005) suggested that ocular diseases of contact lens wearer could be as a result of noncompliance or omission of surfactant cleaning rub and rinse steps, the use of disinfecting solution of marginal efficacy and lenses that attract and rapidly deposit protein. Thus, the lens care regimen is an important factor for consideration on subjects that showed no growth among the daily and extended contact lenses wearers.…”
Section: Discussionmentioning
confidence: 99%
“…The details of this work -collectively referred to as 'The Manchester Keratitis Study' -have been published previously [4][5][6][7][8][9][10] and will be referred to extensively throughout this chapter. The design of this experiment is represented schematically in Figure 24.5.…”
Section: The Manchester Keratitis Studymentioning
confidence: 99%